Youth Disillusionment with Nationalism in Saput’s “Meropani hoinara? yo desh” (“Isn’t this country mine too?”): A Critique of Nepali National Identity - Bhusal, Tilak; Bhattarai, Krishna Prasad (Butwal Campus Journal, 2024)
The main objective of this article is to explore youth disillusionment and the quest for national identity in Prakash Saput's song “Meropani hoinara? yo desh” (“Isn’t this country mine too?”). The lyric of the song reveals the frustrations of young Nepalis who feel marginalized by the political system agonized with corruption and inequality. In particular, the youths articulate a profound sense of betrayal and alienation by questioning the ownership and belonging within their homeland. The article examines how Saput's song serves not only as a reflection of the current socio-political landscape but also as a powerful critique of the systemic failures that hinder the younger generation's aspirations. To examine this issue, the article has employed nationalism as a theoretical insight, especially the ideas of Benedict Anderson, Ernest Gellner and Anthony D Smith to be used for textual analysis. This article posits that "Meropani hoinara? yo desh" resonates as a call for recognition and change, urging everyone to acknowledge the contributions and potential of Nepali youths in shaping a more inclusive national identity